Kebijakan Pemerintah Pada Peningkatan Kualitas Pendidikan Islam di Indonesia : Kebijakan Pemerintah Pada Peningkatan Kualitas Pendidikan Islam di Indonesia - Aynun Nurul Ulufah (Pascasarjana IAIN Ponorogo, 2024)
The purpose of this writing is to describe the Indonesian government's policies in improving the quality of education in Indonesia. The problem of government policy is improving the quality of Islamic education in Indonesia, which is a strategic issue in the development implementation agenda. Educators in schools have a strategic position in the development of students. Because of the task of education, apart from the government, educators also have the obligation to participate in making the nation's life more intelligent. The method the author uses in writing this article is a literature review. The conclusions that can be obtained are, First; facilities and infrastructure as well as educators as one of the most important components of the Indonesian government's policy strategy in the national education system which receives primary attention. Second: The quality of service regarding facilities and infrastructure as well as educators must continue to be improved. Third: the welfare of educators from a material perspective must also receive serious attention.